(untitled) (PHILM. Rivista di filosofia e cinema, 2024)
The article employs the concept of the “Resonance Relationship” to examine the theoretical and practical tensions inherent in the process of artistic creation as it pertains to the practice of film montage. A re-reading of the film Blow-Up will facilitate an examination of the interplay between the two conceptual poles of control and uncontrollability as they manifest in artistic practices. The study will be supported by an analysis of various perspectives on interrelated issues, including the “photographic zoom” as described by Walter Benjamin, Walter Murch’s approach to montage, and the concept of the “aporia of art” as articulated by Theodor W. Adorno in his Aesthetic Theory.